Cooperative Localization of Drones by using Interval Methods - Kenmogne, Ide Flore; Drevelle, Vincent; Marchand, Eric (Acta Cybernetica, 2020)
In this article we address the problem of cooperative pose estimation in a group of unmanned aerial vehicles (UAV) in a bounded error context. The UAVs are equipped with cameras to track landmarks positions, and a communication and ranging system to cooperate with their neighbours. Measurements are represented by intervals, and constraints are expressed on the robots poses (positions and orientations). Each robot of the group first computes a pose domain using only its sensors measurements using set inversion via interval analysis. Then, through position boxes exchange, positions are cooperatively refined by constraint propagation in the group. Results with real robot data are presented, and show that the position accuracy is improved thanks to cooperation.